Interactive statistics for a diverse student population. (4th May 2019) - Hilliam, Rachel; Calvert, Carol
Abstract: Students from many different subject areas are required to study statistics as part of their qualification. The Open University developed a statistics module which could simultaneously be studied by students from a variety of different disciplines, by engaging them with topics which are of interest to everyone, namely money, education and health, rather than being based in the student's own discipline. The module attracts students from a wide variety of backgrounds and has one of the highest retention and pass rates of any OU module at level one. In addition, it has succeeded in successfully teaching a highly visual subject, which includes a wide range of online resources, to all students, including widening participation priority groups. It is hoped this can provide a model for other large service teaching courses, together with providing career and professional development for professional bodies.